The two futures of governing. Decentering and recentering processes in governing: with the introduction of Bob Jessop - Peters, Brainard Guy (Journal of Public Governance, 2012)
Reforms of the public sector have helped create a more efficient and effective public sector, but also have created a number of problems. Both, the New Public Management and “governance” reforms have contributed to the contemporary problems in governing. These problems have been political to a great extent, reflecting the tendency to emphasize administrative rather than democratic values. Governments have begun to react to the real and perceived problems within the public sector by developing a number of “meta-governance” instruments that can help steer public organizations but which involve less direct command and control. This paper addresses the contemporary governance tasks of restoring political direction and policy coherence while at the same supporting the autonomy of public organizations, and the involvement of policy networks, in governing.